Efficacy of cartilage-targeted IGF-1 in a mouse model of growth hormone insensitivity - Tailor, Krishma; van Ree, Janine; Stowe, Timothy; Ventura, Brit; Sisk, Connor; Courtis, Joanna; Camp, Anna; Elzamzami, Fatima; van Deursen, Jan; O’Brien, Robert; Baron, Jeffrey; Lui, Julian C. (Frontiers in Endocrinology, 2025)
Recombinant human IGF-1 is used to treat severe primary IGF-1 deficiency, but this treatment requires twice-daily injection, often does not fully correct the growth deficit, and has important off-target effects. We therefore sought to target IGF-1 to growth plate cartilage by generating fusion proteins combining IGF-1 with single-chain human antibody fragments that target matrilin-3, a cartilage matrix protein. We previously showed that this cartilage-targeting IGF-1 fusion protein (CV1574-1) promoted growth plate function in a GH-deficient (lit) mouse model. Here, we studied CV1574-1 in a second mouse model, C57BL/6 wild-type mice treated with pegvisomant to induce GH resistance. In this model, once-daily injections of CV1574-1 for 5 days partially restored the pegvisomant-induced decrease in growth plate height without increasing kidney cell proliferation. Furthermore, we found that subcutaneous CV1574-1 showed significantly reduced hypoglycemic effect compared to injection of IGF-1 itself. Lastly, to gain mechanistic insights into the role of matrilin-3 targeting, we assessed the ability of CV1574-1 to activate AKT signaling in vitro and found that CV1574-1 caused a prolonged increase in AKT signaling compared to IGF-1 and that this effect was dependent on matrilin-3. Taken together, our findings provide further evidence that cartilage-targeted therapy could provide new pharmacological approaches for the treatment of childhood growth disorders, such as GH-insensitivity syndrome.